Seed Messenger : Understanding the Importance of Trees in Environmental Conservation - Avni Dontulwar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Trees are essential pillars of environmental conservation, playing a vital role in maintaining ecological balance. They absorb carbon dioxide and release oxygen, helping to combat climate change by reducing greenhouse gases. Trees also support biodiversity, providing habitat, food, and shelter to numerous species, thus sustaining diverse ecosystems. Additionally, trees prevent soil erosion, improve water quality by filtering pollutants, and maintain soil fertility through nutrient cycling. Urban areas benefit from trees as they reduce pollution, lower temperatures, and improve air quality, enhancing public health. Trees are also valuable resources for human communities, offering timber, fruits, and medicinal products while fostering cultural and recreational spaces. Despite their importance, deforestation and urbanization continue to threaten global tree cover, leading to ecosystem degradation and biodiversity loss. Therefore, conserving and expanding tree populations is critical for a sustainable future. This paper discusses the multiple roles of trees in environmental conservation, emphasizing the need for robust policies and community efforts to protect these green guardians of our planet.
Keywords: Environmental Conservation; Biodiversity; Climate Change; Deforestation; Ecosystem Restoration